A Novel Neorickettsial Infection in 3 Dogs in the Pacific Northwest. Issue 2 (March 2020) - Pastenkos, Gabrielle; Snekvik, Kevin; Bradway, Dan; Cerchiaro, Ilaria; Mehain, Susan; Krytenberg, Denise; Eckstrand, Chrissy
The genus Neorickettsia includes obligate, intracellular bacteria responsible for diseases including Potomac horse fever caused by Neorickettsia risticii and salmon poisoning disease (SPD) caused by Neorickettsia helminthoeca . The Stellanchasmus falcatus (SF) agent is a member of this genus previously associated only with mild clinical signs in dogs. Between 2013 and 2016, 3 dogs in Washington State (USA) presented with disease suggestive of SPD, but N. helminthoeca was not detected by molecular techniques. Clinical signs included depression, anorexia, and diarrhea. Cytologic examination of aspirates supported a diagnosis of granulomatous lymphadenitis with organisms suggestive of Neorickettsia . Dogs either died or were humanely euthanized due to poor response to therapy. Necropsy findings included lymphadenomegaly and hepatomegaly. Histopathology identified granulomatous and lymphoplasmacytic splenitis, lymphadenitis, enteritis, and hepatitis with extensive necrosis. Neorickettsia DNA was detected using genus-specific primers and direct sequencing showed 100% sequence identity to the SF agent in all 3 dogs. This is the first clinicopathologic description of severe disease in dogs attributed to the SF agent. These findings may suggest the emergence of a novel neorickettsial disease in the Pacific Northwest.